Group B Streptococcus (Streptococcus agalactiae) Screening During Pregnancy - Jahan Ara Saeed (Journal of Rawalpindi Medical College, 2014)
Background:An audit trial was conducted to review our practice of Universal GBS screening for our pregnant patients and its effect on fetal outcome. Methods: In this descriptive study all the patients attending antenatal clinic had their GBS swab performed between 35-37 weeks of pregnancy. Patients were informed about their GBS status on next visit and advised to attend early in labour or in case of rupture of membranes for administration of intra-partum antibiotic prophylaxis. One dose of Benzathine Penicillin 3 mu within 2 hours of delivery to reduce the risk of early onset Group B Streptococcus agalactiae infection. Blood cultures were drawn in all the babies with GBS positive mothers. The cost effectiveness of the screening and treatment were studied by checking for the cost according to the hospital stores department of swab, culture and cost of medication to the patients during this period. Results: There was a total of 2405 deliveries during this period. Two hundred and nine cases were GBS positive. Intrapartum antibiotic prophylaxis [IAP] was given to 48 patients while 161 did not receive any treatment. All the babies had no growth on blood culture. Conclusion: The cost involved in the GBS swab, culture and its treatment clearly indicate that the practice is not cost effective. In view of our audit we have to reconsider our practice of universal screening changed to high risk patient screening only.